The combined approach to solving issues of the flood hazard assessment using water gauge records and spatial data - Vasyl Korbutiak; Dmytro Stefanyshyn; Oleh Lahodniuk; Alina Lahodniuk (Acta Scientiarum Polonorum. Architectura)
The research deals with the combined approach to boost the reliability of hydrological estimates based on a series of observations being supported by spatial data. In particular, the application of various theoretical curves of probability distribution or situations that may occur at submountain sections of rivers (for example, alluvium accumulation or river bed erosion) is considered. Because of the obsolete cadastral data on the riverbeds and catchments, the necessity of the use of remote sensing is substantiated. Assessment of the dynamics of changes in the river cross-section profiles allows making conclusions concerning the direction of the channel deformations – deepening and straitening the river channels or increasing their cross dimensions. This information may complement the assessment of flood protection of the territories.